Development of the Teaching Virtual Clinic in the medical university of Santiago de Cuba - Delfina Durán Rengifo; Nancy María Rodríguez Beltrán; Luisa Francisca Acosta Ortega; Giselle Velez Fernández (Medisan, 2021)
Among the teaching-learning virtual environments figures the Teaching Virtual Clinic that is an educational space of great transcendency in the university context of medical sciences, which contains health situations grouped in different specialties and sections with specific characteristics as for objectives and organization, what favors the integration of teaching activities with or without physical presence, and the social exchange between people that share common problems and interests, with the perspective of the permanent construction of knowledge, starting from very well defined rectors principles, as creating, sharing and collaborating.